PENGEMBANGAN KURIKULUM MENUJU TRANSFORMASI PENDIDIKAN ABAD KE-21 - Nababan, Putri Neta; Fira Wibawanti; Firman Fathulrohman; Sholeh Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The curriculum is the core of the educational system, functioning as a structured guideline that directs all learning processes in a coherent and sustainable manner. However, a gap often exists between the ideal curriculum documents and their factual implementation in the field. This study aims to analyze the basic concepts of curriculum development based on classical and contemporary theories and to formulate a development model relevant to addressing the challenges of 21st-century education. The method used in this article is library research by reviewing various literatures, journals, and policy documents, which were then analyzed using qualitative synthesis of curriculum dimensions. The findings indicate that curriculum development can no longer rely solely on administrative approaches or fragmented grassroots approaches. A cohesive integration between national standards and local flexibility is required. The conclusion of this study recommends the application of a hybrid model approach that combines top-down authority for quality standardization with grass-roots initiative for contextual innovation. The implications of this research demand a paradigm shift for policymakers and educational practitioners to be more adaptive to the hidden curriculum and the dynamics of rapid social change to produce competent and character-filled generations.